The Effect of Baby Massage Classes on Mothers’ Skills in Performing Baby Massage at the Sumartini Maternal and Child Health Clinic in 2026 - Nurul Fadillah; Nova Rati Lova; Maulida Latifah (Public Health Journal, 2026)
Infancy is a critical period for growth and development, and appropriate stimulation should be provided from an early age. One form of stimulation that parents can provide is infant massage. However, some mothers still lack the necessary skills to perform infant massage using the correct techniques, due to limited information, experience, and opportunities for practice. Infant massage classes that combine instruction, demonstrations, and hands-on practice are expected to improve mothers’ skills. This study aims to analyze the effect of baby massage classes on mothers’ skills in performing baby massage at the Sumartini Purwakarta Maternal and Child Health Center (TPMB) in 2026, as well as to analyze the effects of age, occupation, and education on these skills. The study employs a quantitative approach using a one-group pretest-posttest pre-experimental design. The sample consisted of 32 mothers selected using total sampling. Skills were measured before and after the intervention using an observation sheet based on the baby massage standard operating procedure (SOP). Analyses were conducted using univariate and bivariate methods. The Shapiro-Wilk test indicated that the data were not normally distributed; therefore, the Wilcoxon Signed-Rank Test was used with α = 0.05. Before the intervention, 24 respondents (75.0%) were in the unskilled category, 5 respondents (15.6%) were moderately skilled, and 3 respondents (9.4%) were skilled. After the intervention, 27 respondents (84.4%) were in the “skilled” category, 4 respondents (12.5%) were “moderately skilled,” and 1 respondent (3.1%) was “unskilled.” The mean skill score changed from 2.69 (SD 0.644) to 1.06 (SD 0.246). The Wilcoxon test yielded a p-value of 0.000 (p < 0.05). The variables of occupation (p = 0.373), age (p = 0.306), and education (p = 0.138) did not show a significant effect. The study’s conclusion indicates that baby massage classes have a significant effect on improving mothers’ skills in performing baby massage. Learning accompanied by demonstrations and practice can serve as an alternative to help mothers perform baby massage correctly.